Improved soil and tomato quality by some biofertilizer products - Bíró, Borbála; Dudás, Anita; Wass-Matics, Heléna; Kocsis, Tamás; Pabar, Sándor; Tóth, Eszter; Szalai, Magdolna; Kotroczó, Zsolt (Acta Agraria Debreceniensis, 2018)
The use of microbial inoculums is a part of sustainable agricultural practices. Among various bioeffectors, the phosphorus-mobilizing bacteria are frequently used.The objective of this study is to investigate the effect of some industrial biofertilizer inoculums, of containing P-mobilizing bacteria on the quantity and some quality parameters of tomato fruits. Spore-forming industrial Bacillus amyloliquefaciens FZB42 (Rhizovital) as single inoculums and combinations with other Bacillus strains (Biorex) were applied on Solanum lycopersicon Mill. var. Mobil test plant. Soil microbial counts, phosphorus availability, yield and fruit quality, such as total soluble solids (TSS) content and sugars (glucose, fructose) were assessed. The results found that single industrial inoculums of FZB42 product had positive effect on P-availability and fruit quality in the pots. Fruit quality parameters, TSS content, soluble sugars were significantly improved (p